PENGARUH PUSAT PERBELANJAAN TERHADAP PERDAGANGAN DAN JASA DI SEKITARNYA DI KOTA JAMBI - , Setyasmoko Pandu H, M. Sani Roychansyah, S.T., M.Eng., D. Eng, Ir. Agam Marsoyo, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A shopping center becomes an option for consumers to shop thus shopping center becomes one of the center of activities of urban communities. Therefore, shopping center management will conduct various efforts to invite more consumers to come to the shopping center. The centralization of those activities will bring up an opportunity for trades and services around the shopping center. Currently, Jambi City as the center of trades and services has 11 shopping centers. This condition leads to a question, how the shopping center influences the surrounding trades and service sectors. The aims of this research are: (1) to identify the influence of shopping centers on trade and service in surrounding area and (2) to identify the factors that influence the development of trades and services around the shopping center at Jambi City at the moment. This research used deductive-qualitative method and before-after analysis regarding the existence of shopping center. This research conducted interviews on 21 respondents